An evaluation of generalized periodontitis treatment, based on diagnostics of pathological teeth mobility, using periotestometry. Clinical review - Т. І. Matviykiv (Zaporožskij Medicinskij Žurnal)
The aim – to evaluate the effectiveness of the periodontal treatment using the method of periotestometry at the stage of early periodontal pathology diagnostics and record physiological mobility shift into pathological mobility.